Utilizing oleaginous bacteria and fungi for cleaner energy production. (1st December 2017) - Qadeer, Samia; Khalid, Azeem; Mahmood, Shahid; Anjum, Muzammil; Ahmad, Zulfiqar
Abstract: Production of bio-lipid from plants has broadened the vision to search for alternative sources of renewable energy to meet future energy demand. One of the potent alternatives is the production of bio-lipid based fuel using oleaginous microbes capable of using organic substrate as a raw material. Due to high lipid accumulation and potential to grow on a wide variety of substrates, the oleaginous microbes are gaining attention worldwide. In this review, we specifically examined bacteria and fungi capable of accumulating bio-lipids through various biochemical functions with the aim that bio-lipids could be more affordable and increasingly used as decreasing production cost in the future. The lipid accumulation in oleaginous microorganisms is carried out through various biochemical functions that are dependent on several factors. Lipid accumulation in oleaginous bacteria and fungi is carried out under nutrient deficient conditions, especially when the culture medium is depleted of nitrogen. Oleaginous microbes under such nutrient stress environment begin to accumulate lipids in their bodies as a storage molecule for energy reserve. The process is carried out through various enzymes. The key enzymes involved in lipid accumulation are lipases, fatty acid transferases, fatty acid synthetase and wax ester synthase or acyl-CoA diacylglycerol acyltransferase. The main biochemical process in most of the oleaginous microbes is carried out through acetyl Co-A formation, leading to the production of prime compounds for lipid biosynthesis. The literature indicates that oleaginous microbes could be potential candidates for lipid biosynthesis and may play a critical role in meeting future energy requirements of the world.